A stepwise mode of TGFβ-SMAD signaling and DNA methylation regulates naïve-to-primed pluripotency and differentiation - Bingnan Zhao; Xiuwei Yu; Jintong Shi; Shuangyu Ma; Shizhao Li; Haitao Shi; Shoubing Xia; Youqiong Ye; Yongchun Zhang; Yanhua Du; Qiong Wang (Nature Communications)
Abstract The formation of transcription regulatory complexes by the association of Smad4 with Smad2 and Smad3 (Smad2/3) is crucial in the canonical TGFβ pathway. Although the central requirement of Smad4 as a common mediator is emphasized in regulating TGFβ signaling, it is not obligatory for all responses. The role of Smad2/3 independently of Smad4 remains understudied. Here, we introduce a stepwise paradigm in which Smad2/3 regulate the lineage priming and differentiation of mouse embryonic stem cells (mESCs) by collaboration with different effectors. During the naïve-to-primed transition, Smad2/3 upregulate DNA methyltransferase 3b (Dnmt3b), which establishes the proper DNA methylation patterns and, in turn, enables Smad2/3 binding to the hypomethylated centers of promoters and enhancers of epiblast marker genes. Consequently, in the absence of Smad2/3, Smad4 alone cannot initiate epiblast-specific gene transcription. When primed epiblast cells begin to differentiate, Dnmt3b becomes less actively engaged in global genome methylation, and Smad4 takes over the baton in this relay race, forming a complex with Smad2/3 to support mesendoderm induction. Thus, mESCs lacking Smad4 can undergo the priming process but struggle with the downstream differentiation. This work sheds light on the intricate mechanisms underlying TGFβ signaling and its role in cellular processes.